2019
DOI: 10.4322/jms.088315
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zingiber officinale on the Spleen Tissue and Antibody Titer of Broiler Chickens

Abstract: Introduction Increasing the immune system's function of fighting infectious diseases is very important in the poultry industry. Ginger, scientifically known as Zingiber officinale, belongs to the Zingiberaceae family. The use of ginger in the diet of poultry increases serum levels of superoxide dismutase enzymes and glutathione peroxidase, which are considered to be important antioxidant enzymes. The main objective of the present study is to evaluate the effect of ginger on the spleen tissue of broiler chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These results are confirmed by the results of Mona et al (2021) , who reported that normal lymphocytes in the bursa, spleen, and thymus tissue of the propolis-supplemented broilers. Moreover, Taghdisi and Hejazi (2019) found normal lymphocytes in the splenic medulla of ginger-supplemented broilers. In contrast, Ahmed et al (2016) reported depletion of the bursal lymphocyte in broilers supplemented with different doses of Chinese propolis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results are confirmed by the results of Mona et al (2021) , who reported that normal lymphocytes in the bursa, spleen, and thymus tissue of the propolis-supplemented broilers. Moreover, Taghdisi and Hejazi (2019) found normal lymphocytes in the splenic medulla of ginger-supplemented broilers. In contrast, Ahmed et al (2016) reported depletion of the bursal lymphocyte in broilers supplemented with different doses of Chinese propolis.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, Taghdisi and Hejazi (2019) reported significant improvement in the antibody titer of the Ross breed broiler supplemented with ginger powder. According to Sahoo et al (2019) , adding ginger powder did not affect antibodies against ND titer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been shown that ginger extract had a curative effect on macroscopic parameters (wound healing). However, it was not effective on the body and spleen weight change, despite increasing spleen weight in the broiler chickens [ 43 ]. In addition, it could increase the weight change in Japanese quail [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginger can be stated that antioxidants like ginger inhibit the creation of free radicals because of the oxidation of fatty acids, causation a final enhancement in the purpose of the humoral system. This is because ginger comprises antioxidants, which are thought to protect the fatty acids of the humoral immune system ( Taghdisi and Hejazi, 2019 ).…”
Section: Discussionmentioning
confidence: 99%